(untitled) (Research Announcements "Heritage BG", 2025)
Analysing municipal policies related to mineral water resources in Sofia’s city centre area and the main project in that field until the First World War, the Central Mineral Baths, the article elaborates on debates in the city council, main construction challenges, alternative possibilities and others. The text also deals with economic aspects related with the project for contemporary mineral baths in the Bulgarian capital city, and as well on the transfer of knowledge and technologies related to the utilization of mineral waters. The main public bath in the city was built as a result of a long process, accompanied by a number of difficulties and numerous plan changes. Also, the role of architects Emil von Förster and Petko Momchilov is highlighted as the two main authors of the architecture. Despite the variable trajectory in the construction process, it should be noted that the city administration from the very early period recognized the exceptional importance of the mineral water springs as a valuable resource and invested considerable time, efforts and funds for their utilization. References: Stoilova, Yokimov 1998. Stoilova, Lyubinka, Petar Yokimov. Sofiyskite mineralni bani. – Arhitektura, № 6, 26 – 31. Stoilova 2014. Stoilova, Lyubinka. Hronika na edno zabelezhitelno sazidanie: Tsentralnite obsthinski mineralni bani Sofia – hronologiya na proektirane i stroitelstvo Sofia. TSDA, DA-Sofia, f. 1K, op. 1, a.e. 23. TSDA, DA-Sofia, f. 1K, op. 1, a.e. 28, 1. TSDA, DA-Sofia, f. 1423K, op. 1, a.e. 1. DA, DA-Sofia, f. 1423K, op. 1, a.e. 5. DA, DA-Sofia, f. 1423K, op. 1, a.e. 6. TSDA, DA-Sofia, f. 1423K, op. 1, a.e. 13 TSDA, DA-Sofia, f. 1423K, op. 1, a.e. 14.